Ultrastructure and phylogeny of Glugea nagelia sp. n. (Microsporidia: Glugeidae), infecting the intestinal wall of the yellowfin hind, Cephalopholis hemistiktos (Actinopterygii: Serranidae), from the Red Sea - Abdel-Baki, Abdel-Azeem S; Al-Quraishy, Saleh; Rocha, Sonia; Dkhil, Mohamed A; Casal, Graca; Azevedo, Carlos (Folia parasitologica, 2015)
A new microsporidian species of the genus Glugea Thélohan, 1891 parasitising the marine teleost fish Cephalopholis hemistiktos Rüppell, collected from the Red Sea in Saudi Arabia, is described on the basis of microscopic and molecular procedures. Spherical and whitish xenoma were observed adhering to the intestinal wall. The numerous spores contained within these xenoma, were ovoid to pyriform and measured 4.3-6.0 µm (5.1 µm) in length and 1.8-2.9 µm (2.2 µm) in width. The spore's wall was composed of two thick layers, which were thinner in the area contacting the anchoring disk. The latter appeared at the spore's anterior pole, in an eccentric position to the longitudinal axis. A lamellar polaroplast surrounded the uncoiled portion of the polar filament projected to the basal region of the spore, giving rise to 26-29 turns with winding from the base to the anterior zone of the spore. The posterior vacuole, located at the spore's posterior pole, and surrounded by the polar filament coils, was irregular and composed of light material. Molecular analysis of the rRNA genes, including the ITS region, was performed using maximum parsimony, neighbour-joining and maximum likelihood methods. The ultrastructural features observed, combined with the phylogenetic data analysed, suggest this parasite to be a new species of the genus Glugea. This is the first species of this genus to be reported from Saudi Arabia and is herein named Glugea nagelia sp. n.
Keywords: střeva; polymerázová řetězová reakce; Arabia; fylogeneze; Phylogeny; Microscopy; Molecular Diagnostic Techniques; Sequence Analysis; elektronová mikroskopie; diagnostické techniky molekulární; Glugea; geny rRNA; Arábie; Percoidea; Genes, rRNA; mikroskopie; sekvenční analýza; Microscopy, Electron; Spores; Bass; spory; Polymerase Chain Reaction; Intestines